Prevalence of hypertension in pregnancy and its associated sociodemographic factors among mothers aged 15-49 years old in Malaysia - Kishwen Kanna Yoga Ratnam; Mohd Azmi Bin Suliman; Wan Kim Sui; Peter Seah Keng Tok; Muhammad Fadhli Bin Mohd Yusoff (BMC, 2024)
Abstract Background Hypertensive disorders of pregnancy (HDP) pose a substantial public health concern, ranking among the primary contributors to maternal and perinatal morbidity and mortality, impacting around 5-10% of pregnancies. This study aimed to determine the prevalence of HDP and its associated factors among mothers aged 15-49 who recently gave birth within the last two years, throughout Malaysia, informing effective public health and primary care interventions. Methods This study was a part of the national survey on maternal and child health (MCH) also known as the National Health and Morbidity Survey (NHMS) 2022: MCH. This was a cross-sectional study using two stage stratified random sampling design. Data of mothers aged 15-49 years old who recently gave birth within the last two years were selected in this study. This survey utilised a set of structured validated questionnaires administered via face-to-face interviews (using a mobile device). Multiple logistic regression analysis was employed to identify the associated factors for hypertension. Results Among 6 335 participants recruited for this study with an estimated population of 782, 550, the prevalence of HDP among Malaysian mothers aged 15-49 years old who recently gave birth within the last two years was 6.5% (95% CI: 5.76, 7.37). Multiple logistic regression showed that maternal age and ethnicity were significantly associated with hypertension. Advanced maternal age had higher odds of hypertension, with an aOR of 2.18 (95% CI = 1.75, 2.71). In addition, Other Bumiputera had higher odds of hypertension (aOR = 2.71, 95% CI = 1.25, 5.87). Conclusion This study reveals the prevalence of HDP among Malaysian women with children under 2 years old, emphasizing advanced maternal age (above 35) and ethnicity as notable risk factors. It improves understanding of the epidemiology of HDP in Malaysia, offering valuable insights for the development of effective public health strategies and clinical interventions that can help with the control of HDP.